Partial acute transverse myelitis is a predictor of multiple sclerosis in children. (October 2014) - Meyer, P; Leboucq, N; Molinari, N; Roubertie, A; Carneiro, M; Walther-Louvier, U; Cuntz-Shadfar, D; Leydet, J; Cheminal, R; Cambonie, G; Echenne, B; Rondouin, G; et al.
Background: Acute transverse myelitis (ATM) in children is a rare and often severe disease for which there are few known prognostic factors, particularly the subsequent risk of multiple sclerosis (MS) diagnosis. Objectives: To determine the clinical course and prognostic factors after a first episode of ATM in children. Methods: Thirty children below 16 years of age diagnosed with a first neurological episode of ATM were included retrospectively. Clinical evaluation, treatment, laboratory, and MRI data were collected. Results: Median age at onset was 11 years (range 3–15 years). Follow-up data were available for a median of 4 years (range 0.5–16.7 years). Five patients subsequently had a diagnosis of MS (17%), which was associated with acute partial transverse myelitis (odds ratio 5; 95% confidence interval 2.3–11), with a 60% probability of having a relapse at five years ( p < 0.01). The 2011 Verhey criteria correctly identified MS in children with the highest specificity (96%) and sensitivity (80%). Conclusion: Acute partial transverse myelitis and brain MRI abnormalities at initial presentation are significantly predictive of a subsequent diagnosis of MS in children with ATM. These findings suggest that closer brain MRI monitoring after acute partial transverse myelitis might make the earlier introduction of disease-modifying therapies possible.